User Experience of Interactive Assistive Courseware for Low Vision Learners (AC4LV): Initial Round - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (UIKTEN - Association for Information Communication Technology Education and Science, 2017)
This study reports an ongoing projects related to the development of interactive digital learning content which specifically designed catering to needs of low vision learners. Reviews from previous literature indicate that interactive digital learning content particularly for low vision learners is highly scarce. It was found that most of the existing interactive digital learning content focuses on the needs of general students, in which most of this course ware means too little to the low vision learners particularly in terms of information accessibility, navigation ability, and pleasure ability aspects. This study starts the project by designing a conceptual designed model which then validated it through expert review and prototyping method. The prototype is called Assistive Course ware for Low Vision (AC4LV) learners. User Centered Design (UCD) approach has been utilized throughout the development of AC4LV. The main aim of this study is to achieve the usefulness of the prototype to the intended user. Therefore, to investigate the usefulness of AC4LV, it has to be tested on the targeted subjects. Thus, this study presents the initial round of user experience testing related to the subjects’ behaviors and reactions on AC4LV in effort to make it as one of the effective learning tools specifically for low vision children. It is called as user experience I. In the test,eight subjects with the average age nine to 12 were involved. Subjective feed backs were obtained through observation and interview. Overall, it was found that each of the elements in AC4LV is useful to the low vision learners. Future works of the study will report on second round of user experience testing as this study has to achieve the saturated data.